The main problem points in higher education - S. A. Baronin; K. S. Syuzev (Высшее образование в России)
It is obvious that higher education in Russian Federation goes though a growing crisis.Therefore it is vitally important to define its deepest causes and factors. Determination of crisis key points on education market enables more effective and targeted problem solving.